Healthy Living: Beating Barriers to Physical Activity - Jennifer Hillan; Linda B. Bobroff (EDIS)
Being active can help you function better and maintain your independence. It also can reduce your risk for getting some diseases, such as diabetes, and help you manage health problems you may already have. If you’re not active, what’s stopping you from getting started? Read on to learn how to overcome some common barriers! This revised 2-page fact sheet was written by Jennifer Hillan and Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, September 2012.